Prophylactic Treatment of Probiotic and Metformin Mitigates Ethanol-Induced Intestinal Barrier Injury: In Vitro, In Vivo, and In Silico Approaches. (27th September 2021) - Patel, Farhin; Parwani, Kirti; Rao, Priyashi; Patel, Dhara; Rawal, Rakesh; Mandal, Palash
Abstract : Ethanol depletes intestinal integrity and promotes gut dysbiosis. Studies have suggested the individual role of probiotics and metformin Met in protecting intestinal barrier function from injuries induced by ethanol. The objective of the current study is to investigate the potential mechanism by which coadministration of probiotic Visbiome® (V) and Met blocks the ethanol-induced intestinal barrier dysfunction/gut leakiness utilizing Caco-2 monolayers, a rat model with chronic ethanol injury, and in silico docking interaction models. In Caco-2 monolayers, exposure to ethanol significantly disrupted tight junction (TJ) localization, elevated monolayer permeability, and oxidative stress compared with controls. However, cotreatment with probiotic V and Met largely ameliorated the ethanol-induced mucosal barrier dysfunction, TJ disruption, and gut oxidative stress compared with ethanol-exposed monolayers and individual treatment of either agent. Rats fed with ethanol-containing Lieber-DeCarli liquid diet showed decreased expression of TJ proteins, and increased intestinal barrier injury resulting in pro-inflammatory response and oxidative stress in the colon. We found that co-administration of probiotic V and Met improved the expression of intestinal TJ proteins (ZO-1 and occludin) and upregulated the anti-inflammatory response, leading to reduced ER stress. Moreover, co-administration of probiotic V and Met inhibited the CYP2E1 and NOX gene expression, and increase the translocation of Nrf-2 as well as anti-oxidative genes (SOD, catalase, Gpx, and HO-1), leading to reduced colonic ROS content and malondialdehyde levels. The combined treatment of probiotic V and Met also improved their binding affinities towards HO-1, Nrf-2, SLC5A8, and GPR109A, which could be attributed to their synergistic effect. Our findings based on in-vitro, in-vivo, and in-silico analyses suggest that the combination of probiotic V and Met potentially acts in synergism, attributable to their property of inhibition of inflammation and oxidative stress against ethanol-induced intestinal barrier injury.